Health and safety management efforts as correlates of performance in the Nigerian construction industry/Sveikatos ir saugos darbe valdymo pastangos nigerijos statybų pramonėje - Godwin Iroroakpo Idoro (Journal of Civil Engineering and Management, 2008)
This study investigates the level of efforts made by Nigerian contractors to maintain a healthy and safe work environment. The objectives are to determine the level of management efforts made by contractors on H&S and their correlation with H&S performance. To achieve these objectives, a field survey involving a sample of 40 contractors selected by stratified random sampling from the contractors registered with the Federation of Construction Industry of Nigeria was carried out. For the study, 6 H&S management variables and 7 H&S performance variables were selected. The H&S management variables are in compliance with H&S regulations, provision of H&S facilities, structures for managing H&S in head and site offices, provision of PPE and H&S incentives, while the H&S performance variables are respondents’ assessment of the performance of structures for managing H&S in head and site offices, accident, injury, accident per worker, injury per worker and injury per accident rates. Data were collected using structured questionnaires and analysed by mean and Spearman correlation test. The results reveal that contractors’ efforts on structures for managing H&S on site are the best correlates of H&S performance, but their level is low. The levels of contractors’ efforts in provision of PPE, compliance with H&S regulations are high, but these efforts are not correlates of H&S performance. The levels of contractors’ efforts in structures for managing H&S in head office and provision of H&S incentives are low and they have low correlation with H&S performance. The study considers these results as indication that the management efforts made by Nigerian contractors to ensure a healthy and safe work environment are yet to have meaningful impact. It suggests increased efforts on local H&S regulations, structures for managing H&S in both head and site offices and provision of H&S incentives as measures for improving safety in the Nigerian construction industry.